Teachers’ emotional competence and students’ social integration: exploring mediation pathways through teacher-student relationships in elementary classrooms - Rauterkus, Hanna; Hennemann, Thomas; Hagen, Tobias; Krull, Johanna; Nitz, Jannik; Eiben, Katrin; Kulawiak, Pawel Roman; Verbeck, Leonie; Hanisch, Charlotte (Frontiers in Education, 2025)
IntroductionThe Prosocial Classroom Model theorizes that teachers’ emotional competence influences student outcomes through indirect pathways, with teacher-student relationships representing one key mediating pathway. However, empirical evidence testing these specific mediation mechanisms for students’ social integration remains limited.MethodsUsing multilevel mediation analysis, we examined direct and indirect associations between teachers’ emotional competence and students’ social integration in a sample of 43 first-grade teachers and 618 students across 18 German elementary schools. Teachers’ emotional competence was assessed via self-report (EKF), social integration through students’ self-perception (FEESS) and peer nominations, and teacher-student relationship quality from students’ perspectives (SPARTS).ResultsTeachers’ emotional competence showed no significant direct associations with any social integration indicator. However, multilevel mediation analyses revealed a significant indirect pathway through teacher-student closeness for students’ self-reported social integration (indirect effect = 0.022, p = 0.046), while the total effect reached significance (p = 0.048). No mediation effects emerged for peer-nominated acceptance or rejection, indicating construct-specific pathways.DiscussionThese findings provide initial empirical support for the Prosocial Classroom Model’s core proposition that teachers’ emotional competence relates to student outcomes primarily through relationship-mediated rather than direct pathways. While effect sizes are small, results suggest that interventions targeting teachers’ emotional competence may enhance students’ self-perceived social integration by improving teacher-student relationship quality. The differential effects across self-report versus peer-nomination measures highlight the complexity of social integration processes in elementary classrooms.